Role of information and communication technology in development of instruction ‎and science of nursing from the view point of nursing students at Shahrekord ‎Medical Sciences University - ali dehkordi (Guilan University of Medical Sciences, 2006)
Introduction: Information and communication technology (ICT), are strengthening ‎technologies used in nursing sciences. Today, people at any part of the world can receive their ‎required information. But no doubt information and communication technologies had their ‎most effect on educational surroundings. Application of ICT on education has led ‎educational surroundings and science development to become directed toward virtualization. ‎This will lead interpersonal communication for development and expansion of sciences to be ‎performed increasingly through computer. With emergence of internet, this medium was ‎employed as a complement for providing information and education.‎ Objective: This study, designed to study the role of information and communication ‎technology in development of nursing science from the view point of nursing students of ‎Shahrekord Medical Sciences University in ‎‏2005‏‎.‎ Methods: In this descriptive research nursing students of third and fourth year of nursing ‎course (BSC) at Shahrekord medical sciences university were selected using easy sampling ‎procedure. Questionnaire was employed as tool of gathering information. Information was ‎gathered through interviews and student's reporting. Following determination of sampling ‎procedures referring to research site questionnaire of these units were distributed and ‎gathered after completion. To achieve objective, descriptive statistics and SPSS software for ‎data analysis was used.‎ Results: Findings of research showed that majority of research subjects (‎‏59%‏‎) were ‎interested in nursing. (‎‏71%‏‎) majority of research subjects (‎‏93%‏‎) had not passed computer ‎courses and (‎‏12%‏‎) had personal computers. (‎‏95%‏‎) had not passed classic internet courses and ‎‎(‎‏97%‏‎) of students believed that information and communication technology has a very ‎important role in developing nursing education. (‎‏98%‏‎) stated ICT increases level of learning. ‎‎(‎‏88%‏‎) said that ICT leads to promotion of nursing profession. (‎‏77%‏‎) had access to internet.‎ Conclusion: It is recommended that in syllabus of BSN courses at least two units of IT and ‎interest instruction is included for BS nursing students. Also in instructing nursing courses, ‎more attention is paid to role of information technology on learning.‎